Food self-sufficiency: Managing the newly-opened tidal paddy fields for rice farming in Indonesia (A case study in West Kalimantan, Indonesia). Issue 3 (March 2023) - Hatta, Muhammad; Sulakhudin,; Burhansyah, Rusli; Kifli, Gontom C.; Dewi, Dina O.; Kilmanun, Juliana C.; Permana, Dadan; Supriadi, Khojin; Warman, Riki; Azis, Hozin; Santari, Putri Tria; Widiastuti, Dwi P.
Abstract: The Indonesian government continues to develop a sustainable food self-sufficiency program by increasing national food security through an extension program. One of the instruments is by opening new rice fields. The area of new rice fields in Indonesia is 222, 442 ha spreading on the islands of Sumatra, Kalimantan, and Papua. This new rice field is estimated to produce 1.2 million tons of rice per year. In the case of West Kalimantan Province, it has opened new rice fields cover an area of 23, 384 ha, mostly in tidal lands. Expansion of newly-opened rice fields does not increase land productivity. Moreover, rice productivity in the newly-opened paddy fields is only an average of 2 t ha −1 . The low rice productivity is caused by biophysical factors of land in agriculture, and social-economic, and institutional factors of farmers at the village level. Therefore, it is necessary to have a rice farming model in newly-opened rice fields involving farmer groups, researchers, agricultural extension agents, government agencies, the private sector, and banks. The purpose of this study was to present a sustainable rice farming model in the newly-opened tidal rice fields. The results of this study showed that application of the rice farming model in newly-opened tidal rice fields could increase rice productivity from 2 to 5.7 t ha −1 and farmer income of IDR 10.6 million, involving good collaboration among farmer groups and farmer economic organizations supported by banks for sustainability.